2020
DOI: 10.5144/0256-4947.2020.389
|View full text |Cite
|
Sign up to set email alerts
|

Trends in bariatric surgery and incidentalomas at a single institution in Saudi Arabia: a retrospective study and literature review

Abstract: BACKGROUND: Data are lacking on trends in bariatric surgery and the frequency of incidental findings in Saudi Arabia. OBJECTIVE: Report on trends in bariatric surgery as well as our experience in incidental findings along with a literature review (mainly on gastrointestinal stromal tumor). DESIGN: Retrospective chart and literature review. SETTINGS: Academic tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Obesity is a prevalent progressive health problem in Saudi Arabia and bariatric surgery has been recognized to be on the rise as a preferred choice for long-term reduction of weight [ 12 , 13 ]. Studies indicate that DS is a typical side effect of bariatric surgery, with little information about its exact frequency and factors associated with it in different settings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is a prevalent progressive health problem in Saudi Arabia and bariatric surgery has been recognized to be on the rise as a preferred choice for long-term reduction of weight [ 12 , 13 ]. Studies indicate that DS is a typical side effect of bariatric surgery, with little information about its exact frequency and factors associated with it in different settings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a prevalent progressive health problem in Saudi Arabia and bariatric surgery has been recognized to be on the rise as a preferred choice for long-term reduction of weight [ 12 , 13 ]. Studies indicate that DS is a typical side effect of bariatric surgery, with little information about its exact frequency and factors associated with it in different settings [ 13 ]. Therefore, the current study aimed at exploring the prevalence of DS and associated factors in patients who have undergone bariatric surgery in one of the main general hospitals in Jeddah, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus patients with adenomatous polyps on polyp pathology had a greater likelihood of H. pylori infection. It has been reported in the literature[ 16 , 17 ] that this can be because there is an association between BMI and H. pylori infection, and that the two factors can interact with each other. Due to the long-term intake of excessively high calories, the immune environment of their organs is changed, which leads to the expansion of adipose tissues and the activation of macrophages through the secretion of chemokines, subsequently causing a localized inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…( Gudzune et al, 2013 ) RYGB and LSG are the two most common bariatric procedures in Saudi Arabia. ( AlAli et al, 2020 ) Prior research has demonstrated LSG’s utility for treating morbid obesity. ( Aldaqal and Sehlo, 2013 , Ahmed et al, 2017 ) Despite the significant weight loss and reduction of comorbid conditions which follow BS, there are complications and nutritional risks associated with these procedures.…”
Section: Introductionmentioning
confidence: 99%